Measurements of spatiotemporal changes in G-actin concentration reveal its effect on stimulus-induced actin assembly and lamellipodium extension - Kiuchi, Tai (The Rockefeller University Press, 2011)
To understand the intracellular role of G-actin concentration in stimulus-induced actin assembly and lamellipodium extension during cell migration, we developed a novel technique for quantifying spatiotemporal changes in G-actin concentration in live cells, consisting of sequential measurements of fluorescent decay after photoactivation (FDAP) of Dronpa-labeled actin. Cytoplasmic G-actin concentrations decreased by ∼40% immediately after cell stimulation and thereafter the cell area extended. The extent of stimulus-induced G-actin loss and cell extension correlated linearly with G-actin concentration in unstimulated cells, even at concentrations much higher than the critical concentration of actin filaments, indicating that cytoplasmic G-actin concentration is a critical parameter for determining the extent of stimulus-induced G-actin assembly and cell extension. Multipoint FDAP analysis revealed that G-actin concentration in lamellipodia was comparable to that in the cell body. We also assessed the cellular concentrations of free G-actin, profilin- and thymosin-β4–bound G-actin, and free barbed and pointed ends of actin filaments by model fitting of jasplakinolide-induced temporal changes in G-actin concentration.